Ingarden (1893-1970): A Biography. Part 1: In the Masters' Shadow - Kuliniak, Radosław (New Research in the History of Western Philosophy, 2025)
This biography explores the captivating life of Roman Witold Ingarden, a key figure in 20th-century philosophy. In this first English-language biography of the Polish philosopher, readers will discover the struggles and triumphs of a man shaped by mentors such as Husserl and Twardowski, navigating a turbulent world: Part 1: In the Masters' Shadow covers the period up to the outbreak of World War II. Drawing on unpublished archival materials, the book unveils lesser-known facets of Ingarden's life-from his youthful passions to his academic challenges. Written in an accessible style, it invites scholars and general readers alike to connect with Ingarden as both a philosopher and a relatable human being.